2012
DOI: 10.1093/ageing/afs114
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic circumstances, health behaviours and functional limitations in older persons in four Central and Eastern European populations

Abstract: Objectives: to investigate functional limitations and their association with socioeconomic factors in four Central and Eastern European populations.Methods: a cross-sectional study of random population samples in Novosibirsk (Russia), Krakow (Poland), Kaunas (Lithuania) and six Czech towns participating in the HAPIEE study. Functional limitations (classified into tertiles of the SF-36 physical functioning subscale), socioeconomic circumstances and health behaviours were available for 34,431 subjects aged 45–69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
5
13
0
1
Order By: Relevance
“…The results of the study show that women have lower values in all quality of life indicators. These results are consistent with other studies in the literature showing that men receive higher average quality of life than women [15,28,36,37]. Women are likely to experience multiple roles, many at the same time.…”
Section: Social Status Using Individual's Characteristics and Qualitysupporting
confidence: 92%
“…The results of the study show that women have lower values in all quality of life indicators. These results are consistent with other studies in the literature showing that men receive higher average quality of life than women [15,28,36,37]. Women are likely to experience multiple roles, many at the same time.…”
Section: Social Status Using Individual's Characteristics and Qualitysupporting
confidence: 92%
“…The results of the study show that women have lower values in all health-related quality of life indicators. These results are consistent with other studies in the literature showing that men receive higher average health-related quality of life than women [16,35,43,44]. Women are likely to experience multiple roles, many at the same time.…”
Section: Social Status Using Individual's Characteristics and Health-supporting
confidence: 92%
“…The standardised summary score for the Physical Component Score (PCS) of the Short Form 36 (SF-36) Health Survey is population normalised (0 is worst physical health and 100 is best physical health) and was classified by tertiles (≤33, 34–66, >66) as has been used previously 25 26 with a 6-month poor outcome defined using the most severe tertile (≤33). Outcome was defined as poor physical health at 6-month follow-up using the SF-36 PCS because this was the most appropriate physical function outcome score available in both studies, and it has demonstrated good validity and responsiveness in this population.…”
Section: Methodsmentioning
confidence: 99%